Quantitative Investigation of Leaf Photosynthetic Pigments during Annual Biological Cycle of Vitis vinifera L. Table Grape Cultivars - Filimon, R.V.; Rotaru, L.; Filimon, R.M. (South African Journal of Enology and Viticulture, 2016)
Variations in chlorophyll a/b and chlorophyll/carotenoid ratios are indicators of senescence, stress or damage to the photosynthetic apparatus and affect the normal course of plant biological processes. The aim of this work was to investigate the chlorophyll (a and b) and carotenoid content and ratios in the leaves of four Vitis vinifera L. table grape cultivars in the main phenophases of the annual biological cycle. During the annual cycle, the moisture content of the leaves decreased significantly (up to 21%), along with a reduction in leaf area and perimeter. Chlorophyll a and b showed a continuous accumulation until grape véraison, with lower values of the Chl a/b ratio at the beginning of the vegetative period. Carotenoids continued their biosynthesis until grape ripening (for another 30 days), at which stage there was a significant decrease in the chlorophyll/carotenoid ratio (2.62 ± 0.31). At véraison, peroxidase had the most intense activity (0.20 to 0.51 U/mg), possibly because of involvement in chlorophyll degradation, while total phenolic content started to decrease. Grape véraison could be regarded as the starting point of foliage senescence. Moreover, the relationship between total chlorophyll (by extraction) and chlorophyll content index (non-destructive method) was very significant (R2 = 0.92). These results contribute to a better understanding of foliar pigment dynamics and the timing of their decline in order to define the behaviour of table grape cultivars during the annual biological cycle.